MENINGKATKAN PEMAHAMAN TERHADAP SUMBER DAYA MANUSIA DALAM PEMBANGUNAN PEREKONOMIAN INDONESIA - Indah Suprabawati Kusuma Negara (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
The main objective of economic development is to create a more prosperous life for the Indonesian people, physically and mentally. This study aims to increase the reader's understanding of the role of Human Resources in the development of the Indonesian economy. The method used is descriptive analysis method. The conclusion of this study is that the importance of understanding the role of human resources in the nation's economic development greatly supports the spirit of the younger generation in increasing their enthusiasm for learning and improving their quality to become potential human resources and improve public understanding.